PERANAN TEORI HUKUM PENYELESAIAN SENGKETA TERHADAP SENGKETA MAWARIS - Harahap, Syahrini; Muhibbussabry, Muhibbussabry (Smart Education, 2025)
Abstract: The Mawaris conflict is a well-known issue in Indonesia. The scope of inheritance issues pertains to the allocation of property among heirs. The Qur'an delineates the partition of inheritance into two stipulations: mitslu hadzl al-untsayain (two to one) and furudhul al-muqaddarah, which include the fractions 1/2, 1/3, 1/4, 1/6, 1/8, and 2/3; this framework embodies the principle of justice. In addition to the idea of justice, there exists the principle of peace agreements, which aligns with a specific dispute resolution approach known as Problem Solving, signifying the pursuit of an alternative that satisfies both sides. This study aims to elucidate and examine the principles of dispute resolution theory and its impact on the resolution of inheritance conflicts. This research is classified as library research, which entails an examination of literature through the analysis of various texts pertinent to the study, utilizing both primary and secondary sources. Subsequently, examine the applicability and impact of dispute resolution theory on the resolution of inheritance disputes. The discussion concludes that if the distribution of inheritance according to the Qur'anic provisions, adhering to the principle of justice, causes issues for the heirs, it is permissible to employ the principle of a peace agreement or to distribute inheritance outside the Qur'anic guidelines. The outcome of this discussion indicates that if the distribution of inheritance conducted in accordance with the Qur'anic provisions and the principle of justice leads to complications for the heirs, it is permissible to adopt the principle of a peace agreement or to distribute the inheritance outside the Qur'anic stipulations. Keywords: Legal Theory; Dispute Resolution, Mawaris Abstrak: Sengketa mawaris merupakan sengketa yang terkenal di Indonesia. Ruang lingkup masalah warisan berkaitan dengan alokasi property di antara para ahli waris. Al-Qur’an menggambarkan pembagian warisan ke dalam dua ketentuan: mitslu hadzl al-untsayain (dua banding satu) dan furudhul al-muqaddarah, yang mencakup pecahan 1/2, 1/3,1/4, 1/6, 1/8 dan 2/3. Kerangka kerja ini mewujudkan prinsip keadilan. Selain ide keadilan, terdapat prinsip perjanjian damai, yang sejalan dengan pendekatan penyelesaian sengketa tertentu yang dikenal sebagai proble solving, yang menandakan pengejaran alternative yang memuaskan kedua belah pihak. Penelitian ini bertujuan untuk menjelaskan dan mengkaji prinsip-prinsip teori penyelesaian sengketa dan dampaknya terhadap penyelesaian sengketa waris. Penelitian ini diklasifikasikan sebagai penelitian kepustakaan (library research), yang meliputi studi kepustakaan dengan menganalisis berbagai teks yang berkaitan dengan penelitian ini, baik yang bersumber dari sumber primer maupun sumber sekunder. Selanjutnya, mengkaji penerapan dan dampak dari teori penyelesaian sengketa terhadap penyelesaian sengketa waris. Pembahasan menyimpulkan bahwa jika pembagian warisan menurut ketentuan Al-Qur’an yang berpegang pada prinsip keadilan meningmbulkan masalah bagi para ahli waris, maka dibolehkan untuk menggunakan prinsip perjanjian perdamaian atau pembagian warisan di luar pedoman Al-Qur’an. Hasil dari pembahasan ini menunjukkan bahwa jika pembagian warisan yang dilakukan sesuai dengan ketentuan Al-Qur’an dan prinsip keadilan menimbulkan kerumitan bagi para ahli waris, maka diperbolehkan untuk menggunakan prinsip perdamaian atau pembagian warisan di luar ketentuan Al-Qur’an.Kata Kunci : Teori Hukum; Penyelesaian Sengketa, Mawaris